2016
DOI: 10.1177/0018726716642506
|View full text |Cite
|
Sign up to set email alerts
|

Social influence and the invocation of rights: The effects of accountability, reputation and political skill on legal claiming

Abstract: Issues relating to litigation and other forms of employee legal claiming are at the forefront of the practice of human resource management. However, organizational scholars have paid scant attention to this important aspect of organizational life. Underrepresented in this collective research have been investigations into how social influence variables impact the legal claiming process. We add to the understanding of legal claiming by evaluating how perceived levels of accountability, reputation and political s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 57 publications
1
6
0
Order By: Relevance
“…Rehabilitation Act (RA) section 503 and Vietnam Era Veterans’ Readjustment Assistance Act (VEVRAA); Ceplenski, 2014). Organizations are willing to adapt policies to accommodate individuals as they believe there are benefits to doing so, but employers have struggled with employee disclosures (Hall et al, 2016; Rudstam et al, 2012). Therefore, understanding the nature of why individuals may choose not to seek the necessary assistance may be critical to implementing specific changes.…”
Section: Discussionmentioning
confidence: 99%
“…Rehabilitation Act (RA) section 503 and Vietnam Era Veterans’ Readjustment Assistance Act (VEVRAA); Ceplenski, 2014). Organizations are willing to adapt policies to accommodate individuals as they believe there are benefits to doing so, but employers have struggled with employee disclosures (Hall et al, 2016; Rudstam et al, 2012). Therefore, understanding the nature of why individuals may choose not to seek the necessary assistance may be critical to implementing specific changes.…”
Section: Discussionmentioning
confidence: 99%
“…This limited control is “balanced” by forms of social influence within (public) organizations. Civil servants use various tactics of social influence, such as reputation, organizational politics, or impressions management (Hall, Wikhamn, and Cardy 2016, 2255), to affect the behaviors of others. This suggests that it is not only difficult to pinpoint accountability but also that the account giver may affect the audience.…”
Section: Integrating Felt Accountability In Public Administration: Relational and Substantive Aspectsmentioning
confidence: 99%
“…As suggested by role theory, accountability dynamics can be viewed as related to other concepts such as a social influence (Hall et al, 2016), impression management (Ammeter et al, 2004), fear of negative evaluation (Watson & Friend, 1969), and evaluation apprehension (Carver & Scheier, 1981). Because accountabilities evolve over time and are subject to interpersonal influences (Frink & Klimoski, 1998), managers and subordinates often both strive to proactively and reactively impact role signals, events, and design to reconstruct meaning so that it benefits them.…”
Section: A Model Of Managerial Accountability Enactmentmentioning
confidence: 99%
“…Managers primarily use accountabilities to constructively influence subordinates' behavior (Frink & Klimoski, 1998) to facilitate goal attainment. Subordinates, despite having less power in the dyad, can hold significant power in role episodes and actively exert influence over them by weighing and prioritizing accountabilities (Hall et al, 2016;Hall et al, 2017). For example, Ferris (1998, 1999) found that subordinates' goal setting efforts could be used as an active impression management tool.…”
Section: A Model Of Managerial Accountability Enactmentmentioning
confidence: 99%